Desenvolvimento de filmes e recobrimentos multifuncionais a partir de fontes de amido e seu impacto na fisiologia e conservação pós-colheita de frutos - Guimarães, George Henrique Camêlo (2019)
The use of biodegradable starch based films and recoveries goes beyond the conservation of plant products, as films and recoveries alter the physiology of these plant products. Given this, the studies should be directed to an evaluation of the physiological changes of the recovered or packaged products and deepen a discussion about several starch sources that can be used and what are the technological implications for this use. Thus, the objective of this work was to develop multifunctional films and recuperators from different starch sources, as well as to evaluate the impact on the physiology and postharvest conservation of recovered and packaged fruits. Experiments performed to determine starch from different sources, glycerol concentration and essential oils. The methods and procedures for film and recuperator repair have been adjusted to ensure better dispersion and adherence to the fruit surface, but also to produce resistant films with characteristics that allow a modified atmosphere to be generated. “Atmosphere generation modified by biodegradable starchy jackfruit-based starch pouches for blueberry packaging ”And“ Jackfruit Starch Coating Delays Volatile Release and Maintains 'Haden' Mango Flavor ”was burned at Michigan State University in the Department of Horticulture Post-Harvesting Lab and at the School of Packaging Packaging Laboratory and in the experiment “Physiology and quality of 'Tommy Atkins' mangoes fully and partially coated with jackfruit starch associated with essential oils” was developed at the Post Harvest Biology and Technology Laboratory of the Center for Agricultural Sciences at the Federal University of Paraíba. In-depth studies on starches not included are still scarce. In the present work, it was evaluated the use of a seed starch for the reproduction of biodegradable films with different characteristics, as well as its application for the formation of modified atmosphere with potential use for plant products. In addition to the use of starch from jackfruit seeds in the form of films, it has also been studied as coatings. As storage atmosphere modifying agents and influence the release of volatiles, perspiration, respiratory rate and sensory and physical-chemical characteristics.